Viet Nam Alive & Thrive Endline Survey 2014: Households - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
This dataset is the result of the household survey that was conducted to gather data at endline within the context of an overall evaluation of the franchise model for Alive & Thrive (A&T) in Viet Nam. The overall aims of the evaluation were to assess the impact of the franchise model on (1) age-appropriate IYCF practices among children <2 years of age and (2) stunting among children 2-5 years of age. A&T is an initiative funded by the Bill & Melinda Gates Foundation to reduce undernutrition and death caused by suboptimal IYCF practices in three countries (Viet Nam, Bangladesh, and Ethiopia) over a period of six years (2009-2014). The goal of A&T is to reduce avoidable death and disability due to suboptimal IYCF in the developing world by increasing exclusive breastfeeding (EBF) until 6 months of age and reducing the stunting of children under two years of age. A&T applied principles of social franchising within the government health system to deliver the interventions. A&T’s Viet Nam strategy is designed to support improvements in infant and young child feeding (IYCF) in three key ways: (1) improving policy and regulatory environments; (2) shaping IYCF demand and practice; and (3) increasing supply, demand, and use of fortified complementary foods. In order to achieve this, the A&T Viet Nam program has been divided into three main focus areas namely advocacy, community, and the private sector. In addition, a communications component is integrated into each of these focus areas to support their activities. Among several activities, the franchise model is a core initiative of the community model to provide quality nutrition counseling to women and families at health facilities at all levels. Implemented in cooperation with the Vietnamese government and select private clinics, franchises delivered a package of focused IYCF counseling services to pregnant women, lactating mothers, and their families, based on a franchise service package. Focused training and capacity building for healthcare workers were undertaken to enable the health system to provide franchise services. Individualized services were supported through mass media campaigns aimed at generating demand for franchise services and promoting optimal IYCF practices. The impact evaluation used a cluster-randomized controlled design with repeated cross-sectional baseline and endline surveys in the same communes within four provinces, Thai Nguyen, Thanh Hoa, Quang Ngai, and Vinh Long. The endline survey included three components—(i) household survey and anthropometric measurements of children and mothers, (ii) community and health facility assessments survey, and (iii) frontline health workers survey. The household survey data provide information on the main impact indicators (child anthropometry and WHO-recommended IYCF indicators); psychosocial/behavioral determinants (maternal IYCF knowledge, beliefs, self-efficacy and intentions); and client access and exposure to, and utilization of A&T services. It also captured influential underlying factors at the child level (child illness, developmental milestones, hygiene and hand washing), maternal characteristics (education, time constraints, and child care arrangement), as well as household characteristics (social economic status, economic shocks, and food security).